SOSIALISASI BUDAYA ADIL GENDER OLEH ORGANISASI GENDER - Sumiarti Sumiarti; Elya Munfarida (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Abstract: equality and gender justice is a global issue. Along with the awareness of human rights, human beings begin to question and criticize the cultures already established that they perceive as unfair behavior constructor (bias) gender. From this point, then there are many organizations that provoke equality and gender justice. In this paper, the organization is called gender organizations. Gender organizations is a noble mission, to speak out gender equality and justice, but in practice, they experience a harsh challenge. How the strategy of gender culture in socializing gender fair culture, this is the question that became the starting point of this paper. Kata Kunci: Sosialisasi, Budaya Adil Gender, dan Organisasi